Pyroptosis: A New Frontier in Kidney Diseases. (29th April 2021) - Zhang, Ke-jia; Wu, Qi; Jiang, Shi-min; Ding, Lei; Liu, Chao-xia; Xu, Ming; Wang, Ying; Zhou, Yao; Li, Li
Abstract : Pyroptosis is a pattern of programmed cell death that significantly differs from apoptosis and autophagy in terms of cell morphology and function. The process of pyroptosis is characterized predominantly by the formation of gasdermin protein family-mediated membrane perforation, cell collapse, and the release of inflammatory factors, including IL-1 β and IL-18. In recent years, with the rise of pyroptosis research, scholars have devoted time to study the mechanism of pyroptosis in kidney-related diseases. Pyroptosis is probably involved in kidney diseases through two pathways: the caspase-1-mediated canonical pathway and the caspase-4/5/11-mediated noncanonical pathway. In addition, some scholars have identified targets for the treatment of kidney-related diseases from the viewpoint of pyroptosis and developed corresponding medicines, which may become a recommendation for prognosis, targeted treatment, and clinical diagnosis of kidney diseases. This paper focuses on the up-to-date advances in the field of pyroptosis, especially on the key pathogenic role of pyroptosis in the development and progression of kidney diseases. It presents a more in-depth understanding of the pathogenesis of kidney diseases and introduces novel therapeutic targets for the prevention and clinical treatment of kidney diseases.